Effects of beer addition on the fermentation quality and flavor development of pickled peppers - Linzhu Li; Wei Su; Yingchun Mu; Yu Jiao; Ling Chen; Huayan Luo (Food Chemistry: X)
This study explored the effects of beer as a fermentation medium additive, with beer addition levels of 25 % and 50 %, on the fermentation quality and flavor development of pickled peppers. Beer addition resulted in higher pH, reducing sugar, and nitrite levels, as well as improved textural crispness, while reducing total acidity and salinity. Microbial community analysis indicated that Firmicutes, Proteobacteria, and Ascomycota were the dominant phyla. Volatile compounds were predominantly categorized into esters, alcohols, aldehydes, and terpenes; collectively, 37 differential volatile compounds were identified, including 24 esters, 5 aldehydes, 3 alcohols, 3 terpenes, 1 acid, and 1 ketone. Moreover, Spearman correlation analysis revealed that Lactiplantibacillus and Wickerhamomyces exhibited significant correlations with key flavor substances. This study can provide a reference for optimizing the fermentation process of pickled peppers and improving the flavor quality of products.